Long-term outcomes among a cohort of 4296 implantable cardioverter-defibrillator patients: insights from the UMBRELLA study. (14th October 2021) - Briongos Figuero, S; Garcia Alberola, A; Rubio, J; Segura, J M; Rodriguez, A; Peinado, R; Alzueta, J; Martinez Ferrer, J B; Vinolas, X; Munoz Aguilera, R; Perez, M L
Abstract: Background: Large observational real-world studies describing modern implantable cardioverter-defibrillator (ICD) populations with long-term follow-up are lacking. Purpose: To assess the incidence of arrhythmias in a cohort of contemporary patients undergoing ICD implant from 2005 and 2017 and to analyze the arrhythmic risk and mortality according to their clinical profiles. Methods: UMBRELLA (NTC01561144) is a prospective, multicentre, nationwide study of ICD patients followed by remote monitoring. All device information was automatically stored through the remote monitoring system and a blinded review of all the stored arrhythmic episodes was performed. The study outcomes were first appropriate ICD therapy and all-cause death. Results: The study population consisted of 4296 patients (61.9±12.9 years, ischaemic cardiomyopathy (ICM): n=2150, dilated cardiomyopathy (DCM): n=1166, valvular heart disease (VHD): n=119, hypertrophic cardiomyopathy (HCM): n=294, arrhythmogenic right ventricular cardiomyopathy (ARVC): n=71, Brugada syndrome (BS): n=143, long QT syndrome (LQTS): n=43, and adult congenital heart disease (ACHD): n=60)). Primary prevention (PP) was the main indication (n=2758). During a mean follow-up of 46.6±27.3 months, 16, 067 episodes of sustained ventricular arrhythmia (SVA) occurred in 1344 patients. Appropriate ICD therapy was delivered to 85.7% (n=13, 767) episodes of SVA in 1173 patients (27.3% of population). A higher risk of first appropriate ICD therapy was observed in VHD (HR: 1.94, 95% CI: 1.43–2.62), ARVC (HR: 1.84, 95% CI: 1.28–2.66), ICM (HR: 1.51, 95% CI: 1.29–1.78), and DCM (HR: 1.28, 95% CI: 1.07–1.53) whereas patients with HCM (HR: 0.72, 95% CI: 0.54–0.96) and BS (HR: 0.25, 95% CI: 0.14–0.45) were at significantly lower risk (Figure 1A). In multivariate analysis (Table 1), age, gender, atrial fibrillation (AF), secondary prevention, LVEF ≤35%, and QRS width emerged as clinical predictors of appropriate ICD therapy, whereas CRT-D correlated with lower risk. An independently higher risk was found in DCM, VHD, and ARVC, and a lower risk in BS patients. At follow-up, 590 deaths (13.4% of population) were reported. Patients with ICM (HR 3.90, 95% CI: 2.58–5.90), DCM (HR 3.33, CI 95%: 2.18–5.10), and VHD (HR 3.97, CI 95%: 2.25–6.99) had worse prognoses and it was significantly better in BS patients (HR 0.11, 95% CI: 0.01–0.67, p=0.017) (Figure 1B). In multivariate analysis, age, gender, AF, renal failure, diabetes and reduced LVEF, emerged as independent predictors of all-cause death (Table 1). Conclusions: Irrespective of the aetiology, contemporary ICD patients with an arrhythmic substrate derived from left ventricular systolic dysfunction had a similar risk of ICD life-saving interventions and death. Funding Acknowledgement: Type of funding sources: None.